Multi-Modal MRI Analysis with Disease-Specific Spatial Filtering: Initial Testing to Predict Mild Cognitive Impairment Patients Who Convert to Alzheimer’s Disease - Oishi, Kenichi; Akhter, Kazi; Mielke, Michelle; Ceritoglu, Can; Zhang, Jiangyang; Jiang, Hangyi; Li, Xin; Younes, Laurent; Miller, Michael I.; van Zijl, Peter; Albert, Marilyn; Lyketsos, Constantine; et al. (Frontiers in Neurology, 2011)
Background: Alterations of the gray and white matter have been identified in Alzheimer’s disease (AD) by structural MRI and diffusion tensor imaging (DTI). However, whether the combination of these modalities could increase the diagnostic performance is unknown. Methods: Participants included 19 AD patients, 22 amnestic mild cognitive impairment (aMCI) patients, and 22 cognitively normal elderly (NC). The aMCI group was further divided into an “aMCI-converter” group (converted to AD dementia within three years), and an “aMCI-stable” group who did not convert in this time period. A T1-weighted image, a T2 map, and a DTI of each participant were normalized, and voxel-based comparisons between AD and NC groups were performed. Regions-of-interest, which defined the areas with significant differences between AD and NC, were created for each modality and named “disease-specific spatial filters” (DSF). Linear discriminant analysis was used to optimize the combination of multiple MRI measurements extracted by DSF to effectively differentiate AD from NC. The resultant DSF and the discriminant function were applied to the aMCI group to investigate the power to differentiate the aMCI-converters from the aMCI-stable patients. Results: The multi-modal approach with AD-specific filters led to a predictive model with an area under the receiver operating characteristic curve (AUC) of 0.93, in differentiating aMCI-converters from aMCI-stable patients. This AUC was better than that of a single-contrast-based approach, such as T1-based morphometry or diffusion anisotropy analysis. Conclusion: The multi-modal approach has the potential to increase the value of MRI in predicting conversion from aMCI to AD.